2016
DOI: 10.2355/tetsutohagane.tetsu-2015-096
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling for Strain Hardening of Two-phase Alloys with Dispersion of Hard Fine Spherical Particles

Abstract: Synopsis :Plasticdeformationanddislocationaccumulationindispersionhardeningalloysarenumericallyanalyzedbyacrystalplasticityfiniteelement technique and work hardening characteristics are discussed. The critical resolved shear stress for slip system is given by the extended expression of the Bailey-Hirsch type model which include the Orowan stress as size effect of microstructure. Work hardening of slip system is estimated by statistically stored dislocation (SSD) density. Increment of the SSD density is evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The clp, that is a code for three-dimensional CPFE analysis developed by Ohashi, 10,2023) is employed in this study. The clp was employed for the analysis of the deformation of materials with face-centered cubic structures, 2327) bcc structures, 28,29) and hcp structures. 30,31) The constitutive equations employed in this study are shown below.…”
Section: Numerical Procedures For Crystal Plasticity Analysismentioning
confidence: 99%
“…The clp, that is a code for three-dimensional CPFE analysis developed by Ohashi, 10,2023) is employed in this study. The clp was employed for the analysis of the deformation of materials with face-centered cubic structures, 2327) bcc structures, 28,29) and hcp structures. 30,31) The constitutive equations employed in this study are shown below.…”
Section: Numerical Procedures For Crystal Plasticity Analysismentioning
confidence: 99%
“…Details of this effect were discussed elsewhere for single phase material 19) and applied also to two-phase microstructure. 20) In this paper, the length scale d is assumed to be equal to lamellar thickness 1,2) when we evaluate the CRSS of the ferrite layer. For the evaluation of CRSS of cementite layers, on the other hand, the Orowan stress is not included because dislocations are supplied from ferrite layers 7) before dislocation sources inside the cementite layers are activated and the curvature radius of the dislocation transferred from the ferrite layer is assumed to be sufficiently large compared to the lamellar thickness, that is, d→∞.…”
Section: Dislocation Density Based Constitutive Equationsmentioning
confidence: 99%
“…It was used to clarify scale dependent mechanical properties of single-phase polycrystalline model 19) and two-phase material model with precipitate. 20) In this paper, we examine mechanical properties of simplified models of the pearlite steel wire by the crystal plasticity analysis. Models are composed of three-layers; a ferrite lamella is sandwiched by two cementite lamellae.…”
Section: Introductionmentioning
confidence: 99%
“…The technique often employed is to just use the mean free path of a pure and single-crystal material and introduce a proportionality constant that expresses the reduction of the mean free path by other kinds of obstacles, Λ = DΛ pm , where Λ pm is the mean free path of pure single-crystal material and D is a constant, which decreases with increasing number and strength of obstacles; however, it usually becomes just a fitting parameter without any physical meaning [37]. Okuyama and Yasuda suggested to apply the shortest Λ of obstacles when several obstacles are present [38,39], but that idea makes the value of Λ homogeneous, although it should vary depending on the position of dislocations and obstacles in actual steels.…”
Section: Introductionmentioning
confidence: 99%